The Effect Of The Use Of Audio Visual Media (VCD) And Audio Media On Achievements Learning Arabic Reviewed From Student Achievement Motivation - Sarimurni, Yulinda (Yayasan Darusssalam Bengkulu, 2020)
The purpose of this study was to determine: (1) The difference in the influence of the use of VCD learning media with audio media on learning achievement in Arabic. This study used a quantitative method with an experimental approach with a 2 x 2 factorial design and descriptive analysis of data presentation. The data analysis technique used was the Two-Way Analysis of Variance (ANOVA) Technique. Prior to the analysis, the validity test was carried out with Product Moment correlation and reliability using Spearman Brown. The results of the research trial showed that all research variables were valid and reliable before testing the hypothesis.Hypothesis test results and research conclusions show: (1) there is a significant difference in learning achievement in Arabic between those who learn with VCD media and AUDIO media. VCD media resulted in higher Arabic learning achievement compared to AUDIO media. price P = 0.000 <0.05. This means that the first statistical hypothesis (Ho) is rejected. And H1 is accepted. The average difference between VCD media and AUDIO media, the results of the analysis show that students with VCD learning media have an average score of Arabic learning achievement of 80.70, as for the group of students with AUDIO learning media the average score of Arabic learning achievement is 71.20. It can be concluded that the results of the Arabic learning achievement test of students taught using VCD media are higher than the AUDIO media; (2) There is a significant difference in the effect of learning achievement in Arabic between those who have high and low achievement motivation. Students with high achievement motivation have better achievement in learning Arabic than students with low achievement motivation. This is evidenced by the price P = 0.000 <0.05. This means that the first statistical hypothesis (Ho) is rejected. This means that the first statistical hypothesis (Ho) is rejected. And H1 is accepted. Difference in mean between high and low achievement motivation. The results of the analysis showed that the group of students with high achievement motivation had an average score of Arabic learning achievement of 78.00 while the average score of learning achievement in Arabic with low achievement motivation was 73.90. It can be concluded that the Arabic learning achievement scores of students who have high achievement motivation are better than students who have low achievement motivation ;; (3) There is an interaction between learning media and achievement motivation on learning achievement in Arabic. Price P = 0.000 <0.05. This means that the first statistical hypothesis (Ho) is rejected, then the H1 hypothesis is accepted. This means that there is an interaction between the influence of the use of learning media and achievement motivation on the achievement of learning achievement in Arabic. VCD learning is equally effective for students who have high achievement motivation and students who have low achievement motivation.